Testing soil fertility, potato (Solanum tuberosum) production and residual effect on green beans (Phaseolus vulgaris) performance using different rates and mixtures of compost and mineral fertilizer - Temgoua, Emile; Ntangmo Tsafack, Honorine; Azinwi Tamfuh, Primus; Ndzana, Georges Martial (Journal of plant nutrition, 2023)
Compost has a long-lasting action on soils to sustain crop production but very few scientific works have demonstrated these agronomic aspects. The present work aims to study the effect of different rates and mixtures of compost and a mineral fertilizer on a humic gleysol fertility, potato (Solanum tuberosum L.) yield and the residual effect on green beans (Phaseolus vulgaris) production in the Cameroon Western Highlands. A first field trial was conducted on potato followed by green beans a year after (without additional fertilization). The experimental design was a split-plot with three replications. The primary factor was compost alone at 4 levels (0, 20, 30 and 40 t ha-1) and the secondary factor was mineral fertilizer application rates at two levels (0 and 350 kg ha-1). The soil samples for each experimental unit were analyzed before and after the experiments. The main results revealed that compost alone at 20 t ha-1 yielded more tubers (15 t ha-1) with probably an ideal rate for potato tubers production (largest diameter, > 40 mm). The combination of compost and the mineral fertilizer had a significant effect only on the proportion of tubers having average diameter (between 25 and 40 mm). During the first year, the compost improved the soil chemical properties notably pH-H 2 O, total nitrogen, organic carbon, C/N ratio, Cation exchange capacity and exchangeable Mg. Compost at 30 t ha-1 yielded an additional 5 t ha-1 of green beans in the second year, meanwhile the mineral fertilizer alone revealed no residual effect.